ACRYLAMIDE: A POSSIBLE RISK FACTOR FOR CARDIAC HEALTH - Singh, Taranbir; Kushwah, Ajay Singh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Acrylamide (ACR) is an important industrial chemical agent also a food contaminant formed when food rich in carbohydrates is processed at high temperatures (120Â°C) such as cooking, frying, roasting, toasting, and baking. It happens when amino acid asparagine reacts with sugars, especially glucose and fructose as a result of the Maillard reaction. Its potential to cause damage to humans and animals makes it a cause for concern. After its outbreak in 2002, extensive study has been going on to prevent its formation in food. Neurological effects are by far well established for ACR along with systemic toxic effects. Diet contributes to the high proportion of ACR intake on daily basis; other exposure media are occupational, environmental, and smoking. A number of studies justifying ACR cardiotoxicity, its clear mechanism and its relevance to humans are less, but some research papers suggest the possibility of cardiotoxicity or developmental cardiotoxicity. In this review, ACR cardiac toxic effects and mechanism pathway have been discussed along with mitigation strategies.